The two dimensional fold test in paleomagnetism using ipython notebook. (January 2016) - Setiabudidaya, Dedi; Piper, John D.A.
Abstract: One aspect of paleomagnetic analysis prone to controversy is the result of the fold test used to evaluate the age of a magnetisation component relative to the age of a structural event. Initially, the fold test was conducted by comparing the Fisherian precision parameter (k) to results from different limbs of a fold structure before and after tilt adjustment. To accommodate synfolding magnetisation, the tilt correction can be performed in stepwise fashion to both limbs simultaneously, here called one dimensional (1D) fold test. The two dimensional (2D) fold test described in this paper is carried out by applying stepwise tilt adjustment to each limb of the fold separately. The rationale for this is that tilts observed on contrasting limbs of deformed structure may not be synchronous or even belong to the same episode of deformation. A program for the procedure is presented here which generates two dimensional values of the k-parameter visually presented in contoured form. The use of ipython notebook enables this 2D fold test to be performed interactively and yield a more precise evaluation than the primitive 1D fold test.